Memory and Executive Function Development in Baby 12-24 Months: A Screening Method by Mothers - Elga Andriana; Ammik Kisriyani; Hanifah Nurul Fatimah (SEAMEO CECCEP, 2023)
The development of memory and executive function in infants is significant for the development of the same aspects at a later stage since during this stage of development, infants are actively developing their core executive function and memory skills. However, research on these two aspects in infants aged 12-24 months in the Indonesian context is still rare. Furthermore, the availability of screening instruments that can be used by mothers to monitor the development of the two aspects is limited. This study aims to develop a method of screening on memory development and executive function that mothers can use for their babies aged 12-24 months. By knowing their child's development in the domain-specific exhibited by the Deferred imitation (DI) task and the A-not-B task, mothers can better understand and obtain feedback regarding their child's development milestones, particularly memory development and executive function. Mothers (N=21) who were involved in this study, filled in pre and post-tests on memory and executive function development, received training to conduct screening by carrying out those 2 tasks to their babies. The mothers were asked to fill in the maternal responsiveness scale to find out the extent of the mother's response rate during interactions with their babies and to see the relationship between their responsiveness and the results of the screening. This study employed a within-subject pre-and posttestdesign. Data were analysed both quantitatively and qualitatively. Qualitative data were gathered through Focus Group Discussion to explore the experiences of mothers when conducting tasks and screening on their babies. The results of this study indicate that the screening method can help maternal participants identify the emergence of memory abilities and executive skills. The screening method used is quite easy and can be carried out by the participants in daily life. However, they need to read the module several times to understand the procedures. Additional analysis showed that maternal responsiveness was associated with a child's better ability to shift from condition A to condition B, but did not confirm an association with DI.